Complaint as a subject of feminist analysis and tool of institutional critique - Magdaléna Michlová (Gender a Výzkum)
The subject of this review is "Ahmed, S. 2021. Complaint! Durham: Duke University Press". The paper introduces Sara Ahmed as a proponent of queer phenomenology and an academic activist involved professionally and personally in combating gender-based violence in academia, mainly by examining complaints as a subject of a phenomenological analysis as well as as a tool of an institutional critique. Ahmed's main research questions and conclusions are presented in the paper, and the aims of the author are critically reflected upon.